2019
DOI: 10.1101/631986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zinc finger RNA binding protein Zn72D regulates ADAR-mediated RNA editing in neurons

Abstract: 15Adenosine-to-inosine RNA editing, catalyzed by ADAR enzymes, alters RNA sequences from 16 those encoded by DNA. These editing events are dynamically regulated, but few trans regulators 17 of ADARs are known in vivo. Here, we screen RNA binding proteins for roles in editing regulation 18 using in vivo knockdown experiments in the Drosophila brain. We identify Zinc-Finger Protein at 19 72D (Zn72D) as a regulator of editing levels at a majority of editing sites in the brain. Zn72D both 20 regulates ADAR protein… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…We used ExOrthist to compare sets of exons regulated by the splicing factor Nova in mouse and fruitfly. For this purpose, we ran vast-tools [27] to obtain changes in inclusion levels (ΔPSIs) for all exons upon Nova2 depletion in mouse embryonic cortex [39] and upon knockdown of the fruifly ortholog ( ps ) in whole adult brains [40]; we then defined as Nova -dependent exons in each species those with a |ΔPSI| > 15 (827 in mouse and 407 in fruifly, respectively; Fig. 5B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used ExOrthist to compare sets of exons regulated by the splicing factor Nova in mouse and fruitfly. For this purpose, we ran vast-tools [27] to obtain changes in inclusion levels (ΔPSIs) for all exons upon Nova2 depletion in mouse embryonic cortex [39] and upon knockdown of the fruifly ortholog ( ps ) in whole adult brains [40]; we then defined as Nova -dependent exons in each species those with a |ΔPSI| > 15 (827 in mouse and 407 in fruifly, respectively; Fig. 5B).…”
Section: Resultsmentioning
confidence: 99%
“…To identify Nova -dependent exons, we run vast-tools v2.5.1 for two datasets characterized by deficiency of Nova orthologs in each species. In particular, we used an experiment with Nova2 depletion in mouse embryonic cortex at the E18.5 stage [39] and another one with downregulation of pasilla ( ps ) in adult fly whole brains [40]. To obtain inclusion levels for all exons, we employed vast-tools align and combine with default parameters for mm10 and dm6 (VASTDB libraries: vastdb.mm2.23.06.20.tar.gz and vastdb.dme.23.06.20.tar.gz) [27].…”
Section: Methodsmentioning
confidence: 99%
“…It revealed the possible multi-regulators of A-to-I RNA editing. From previous literature, these diverse regulatory mechanisms probably include genetic variations (67,68), splicing efficiency (69,70), and RNA binding proteins (71,72). For a functional RNA editing candidate (CAediting_1478179 of APOL1) proposed in this study, we also discovered its differential editing frequencies among the genotyping groups of three single nucleotide variations in the KIRC cancer type (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Alternatively, as suggested by differences in effect size, additional regulatory factors may be involved. Numerous studies spanning the past decade have consistently concluded that changes in ADAR expression do not fully account for differences in the extent of A‐to‐I editing and the identification of such regulatory factors remains an active area of research for the field (Hood et al., 2014; Li & Church, 2013; Porath et al., 2019; Sapiro et al., 2020; Schaffer et al., 2020; Tan et al., 2017; Wahlstedt et al., 2009).…”
Section: Discussionmentioning
confidence: 99%